(untitled) (Research, Society and Development, 2023)
Objective: to identify the limiting factors for the effectiveness of the process of dehospitalization and the functioning of home care in Brazil and its associated factors. Methods: An integrative review of the literature was carried out with a qualitative character, with the following guiding question: "what are the limiting factors for the effectiveness of dehospitalization in Brazil, what is the contribution of humanized assistance in this process and what are the difficulties and potentialities of this strategy for continuity of care? "Dehospitalization" AND "Home care" were used as descriptors in health sciences (DECS) in the Google Scholar search engine (Google Scholar). The final sample consists of 11 studies. Results: the main evidence found in the literature related to dehospitalization is related to the individualization in the organization and planning of this process and the conduct of the multidisciplinary team aimed at the elaboration of a therapeutic plan aimed at home care with approximation between professionals of the multidisciplinary team and the family, providing guidance and training. Factors such as user, caregiver and family recognition, identifying difficulties and seeking ways to overcome them effectively and creatively are essential to guarantee the functionality of home care. Final Considerations: The dehospitalization process proved to be complex and dependent on relationships between the institution’s management, health professionals, users, their families and the health care network (RAS). It was observed that during the dehospitalization process, the family should be valued and receive attention and support from the interdisciplinary team, in addition to the necessary training to act as capable caregivers.